Values in Heritage Management: Emerging Approaches and Research Directions - Susan Macdonald (Getty Publications, 2019)
Over the last fifty years, conservation professionals have confronted increasingly complex political, economic, and cultural dynamics. This volume, with contributions by leading international practitioners and scholars, reviews how values-based methods have come to influence conservation, takes stock of emerging approaches to values in heritage practice and policy, identifies common challenges and related spheres of knowledge, and proposes specific areas in which the development of new approaches and future research may help advance the field.